2010
DOI: 10.1017/cbo9780511817779
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Language

Abstract: Language, more than anything else, is what makes us human. It appears that no communication system of equivalent power exists elsewhere in the animal kingdom. Any normal human child will learn a language based on rather sparse data in the surrounding world, while even the brightest chimpanzee, exposed to the same environment, will not. Why not? How, and why, did language evolve in our species and not in others? Since Darwin's theory of evolution, questions about the origin of language have generated a rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 712 publications
(123 citation statements)
references
References 1,123 publications
2
120
0
1
Order By: Relevance
“…Over the course of training, the monkeys learned to control the intensity and duration of a species-typical coo vocalization. Overall, these empirical results make it clear that, given an adequate number of trials and time, primates can at least acquire the ability to voluntarily ''gate'' production of species typical vocalizations (Fitch 2010).…”
Section: Vocal Controlmentioning
confidence: 85%
See 1 more Smart Citation
“…Over the course of training, the monkeys learned to control the intensity and duration of a species-typical coo vocalization. Overall, these empirical results make it clear that, given an adequate number of trials and time, primates can at least acquire the ability to voluntarily ''gate'' production of species typical vocalizations (Fitch 2010).…”
Section: Vocal Controlmentioning
confidence: 85%
“…An issue of particular interest is Koko's control over vocalization, since previous research has suggested that apes have less volitional control over their larynx compared to their breath and supralaryngeal articulators (Fitch 2010). While the majority of Koko's VBBs were unvoiced, she does appear to wield some voluntary control over her larynx.…”
Section: Discussionmentioning
confidence: 99%
“…I will refer to these core traits derived components of language (relative to our last common ancestor with chimpanzees), or BDCLs.^By our current understanding of ape cognition and communication, the set of DCLs contains at least three separable components (see The derived components section): complex vocal learning, hierarchical syntax, and complex semantics/pragmatics (cf. the Bthree Ssô f speech, syntax and semantics in Fitch, 2010).…”
Section: The Multicomponent Approachmentioning
confidence: 99%
“…Interest in language evolution has surged in the past two decades (Berwick, Friederici, Chomsky, & Bolhuis, 2013;Carstairs-McCarthy, 1999;Christiansen & Kirby, 2003;Dunbar, 1996;Fitch, 2010;Hauser, Chomsky, & Fitch, 2002;Pinker & Bloom, 1990;Számadó & Szathmary, 2006;Tallerman & Gibson, 2011;Yang, 2013). This surge has been accompanied by fundamental progress in our understanding of this difficult multidisciplinary problem.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that in an environment where selection favored the development of more sophisticated communication in ancient hominins, the benefits of the vocal channel of communication provided a selective pressure for anatomical and neurological adaptations to increase the degree of control over vocalization and the range of sounds that could be produced (Fitch 2010;Simonyan 2014). The genetic basis for these changes is not yet known.…”
Section: Emergence Of Language In the Human Lineagementioning
confidence: 99%